2021
DOI: 10.1080/02723638.2021.1959778
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic segregation in European cities. A comparative study of Brussels, Copenhagen, Amsterdam, Oslo and Stockholm

Abstract: The purpose of this study is to compare socioeconomic segregation patterns and levels in Brussels, Copenhagen, Amsterdam, Oslo, and Stockholm with uniform measurements. Socioeconomic segregation is a persistent reality in European cities that may have negative effects on social cohesion and individual outcomes. Previous research has been hampered by conceptual and methodological shortcomings, preventing comparable studies of segregation. We use harmonized datasets from 2011 containing geocoded indicators based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 73 publications
0
32
0
1
Order By: Relevance
“…They claim that racial discrimination has resulted in a high concentration of ethnic and racial minority groups in neighbourhoods with high crime levels, social disorder, unemployment rates, poor public health and services, and high environmental injustice (Wilson, 2012). With the global city thesis of social polarisation, socioeconomic segregation, which means the residential sorting of socioeconomic groups by income (Haandrikman et al, 2021), working status (Ng et al, 2021), and occupation (Smith et al, 2020) have become a significant dimension of residential segregation (Reardon et al, 2018;Van Ham et al, 2021). Disadvantaged minorities face unequal access to valued resources (e.g., education and job markets) critical to their life chances and social mobility.…”
Section: Spatial Context Of Segregationmentioning
confidence: 99%
“…They claim that racial discrimination has resulted in a high concentration of ethnic and racial minority groups in neighbourhoods with high crime levels, social disorder, unemployment rates, poor public health and services, and high environmental injustice (Wilson, 2012). With the global city thesis of social polarisation, socioeconomic segregation, which means the residential sorting of socioeconomic groups by income (Haandrikman et al, 2021), working status (Ng et al, 2021), and occupation (Smith et al, 2020) have become a significant dimension of residential segregation (Reardon et al, 2018;Van Ham et al, 2021). Disadvantaged minorities face unequal access to valued resources (e.g., education and job markets) critical to their life chances and social mobility.…”
Section: Spatial Context Of Segregationmentioning
confidence: 99%
“…The Productivity Commission noted an increase over recent decades in the time taken to process applications. Legislated 12-week deadlines for processing building and zoning applications are not long by international standards (Gyourko and Molloy, 2014 [61]). Municipalities tend, on average, to stick to these deadlines, too (Figure 18).…”
Section: Making Planning and Zoning Quicker Cheaper And More Predictablementioning
confidence: 99%
“…Recent studies on socio-economic segregation in European capital cities (Tammaru et al, 2015) revealed that even though the levels of segregation in Europe are still relatively low compared with other parts of the world, ‘the spatial gap between poor and rich is widening’ (Marcińczak et al, 2015b: 358). The rapidly growing body of literature on social polarisation and increasing residential segregation (Friesenecker and Kazepov, 2021; Haandrikman et al, 2021; Hamnett, 2021; Hedberg and Tammaru, 2013; Maloutas, 2012; Maloutas and Botton, 2021a; Ouředníček et al, 2015; Tammaru et al, 2015, 2021; Van Ham et al, 2020, 2021) indicates the assumed social impacts of segregation.…”
Section: Introductionmentioning
confidence: 99%